ANALYSIS OF CRITERIA OF MATHEMATICAL MODELS OF CIRCULATING WATERS - Matbabayev , M.M.; Numonjonov , Sh.D. (Educational Research in Universal Sciences, 2023)
In such IAAs, hot and cold heat carriers directly touch each other and then mix. For example, high-temperature steam from the boiler unit is mixed with cold or warm water, and then transferred to consumers. Such IAAs include coolers, deaerators, scrubbers, and other devices.